The effect of individualised self-talk during imagery on netball shooting performance - Osman, Norhafizah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Previous studies showed that imagery is widely used for the enhancement of sports performance. Some findings showed that individualised self-talk can overcome anxiety, thus, improve athletes' performance. Positive self-talk is believed to enhance motivation, and concentration. In contrast, negative self-talk is deemed to have a negative effect on performance as it fosters self-doubt and anxiety. The aim of this study is to investigate the effect of using individualised self-talk during imagery on netball shooting performance. A total of n = 28 female participants participated in this study. They were assigned to two groups, a) Self-talk during imagery intervention (n= 15 ) and b) Control group (n= l3). A pre-test netball shooting performance was conducted before the intervention, and a post-test netball shooting performance was conducted after participants completed their 12 sessions of imagery intervention with individualised self-talk. Participants' profiles were measured using Sport Imagery Ability Measurement (SIAM), Rosenberg Self- Esteem Scale, and Revised Competitive State Anxiety Inventory 2 (CSAI-2R). The results showed that the participants had acceptable imagery skills, on which they scored a total mean score of 720.35 over 1200 points. There were significant differences between pre to post measurement four weeks for cognitive state anxiety scores (p = 0.009) but there was no significant difference in somatic anxiety (p = 0.986) and self-confidence scores (p = 0.971) respectively. Furthermore, that there was no significant difference between both groups on netball shooting performance (p = 0.735). In conclusion, there were some positive effects of using individualised self-talk during imagery intervention on netball shooting performance.